Sarcoidosis in the United States Military Health System - Parrish, Scott C; Lin, Thuy K; Sicignano, Nicholas M; Lazarus, Angeline A (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Rationale: Sarcoidosis is an inflammatory disorder of unclear etiology with historical significance in the U.S. Department of Defense (DoD). Objectives: This study sought to characterize the sarcoidosis population within the DoD Military Health System (MHS). Methods: Adult patients with sarcoidosis were identified in the DoD MHS database from 01-JAN-2004 through 31-DEC-2013. Patients required ≥3 encounters with a sarcoidosis diagnosis and continuous MHS eligibility. Index was defined as date of first sarcoidosis encounter. Comorbidities were assessed within the pre-index and follow-up periods. Additionally, a subset of sarcoidosis patients was identified as having conditions that can be associated with cardiac sarcoidosis. Measurements and Main Results: The final sarcoidosis cohort was 9,908 patients, 57% female, and had a mean (SD) age of 53.1 (13.6) years. The region with the largest population was the east coast (45.6%). The top 5 pre-index comorbidities were hypertension (51.7%), fatigue (27.0%), anemia (21.4%), diabetes, type II (19.6%), and coronary heart disease (16.5%). Prevalence of the following conditions increased ≥2-fold from pre-index to follow-up: leukocytopenia, pulmonary hypertension, chronic kidney disease, thrombocytopenia, hypercalcemia, venous thromboembolism, congestive heart failure, seizure disorder, stroke/TIA, hypercalciuria, and arthritis. Of the sarcoidosis cohort, 21.8% (n=2,164) were identified as having cardiac conditions that can be associated with cardiac sarcoidosis. The top conditions in this cohort were cardiac arrhythmia (75.6%), congestive heart failure (20.4%), and cardiomyopathy (13.6%). Conclusions: The MHS has a large population of sarcoidosis patients, of which 22% had cardiac conditions that can be associated with granulomatous inflammation of the heart. Prevalence of numerous comorbid conditions increased after sarcoidosis diagnosis.